2014
DOI: 10.1037/a0036389
|View full text |Cite
|
Sign up to set email alerts
|

Mood impairs time-based prospective memory in young but not older adults: The mediating role of attentional control.

Abstract: The present study examined age-by-mood interactions in prospective memory and the potential role of attentional control. Positive, negative, or neutral mood was induced in young and older adults. Subsequent time-based prospective memory performance was tested, incorporating a measure of online attentional control shifts between the ongoing and the prospective memory task via time monitoring behavior. Mood impaired prospective memory in the young, but not older, adults. Moderated mediation analyses showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
5
27
3
Order By: Relevance
“…For example, Levant et al (2015) found that the mediation effect of endorsement of masculinity ideology on sleep disturbance symptoms via energy drink use was significantly different between white and racial minority groups. Schnitzspahn et al (2014) found that time monitoring mediated the effect of mood on prospective memory in young adults, but not in old adults. Gelfand et al (2013) showed that the effect of cultural difference (US vs. Taiwan) on the optimality of negotiation outcome is mediated by harmony norm when negotiating as a team but not when negotiating as solos.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Levant et al (2015) found that the mediation effect of endorsement of masculinity ideology on sleep disturbance symptoms via energy drink use was significantly different between white and racial minority groups. Schnitzspahn et al (2014) found that time monitoring mediated the effect of mood on prospective memory in young adults, but not in old adults. Gelfand et al (2013) showed that the effect of cultural difference (US vs. Taiwan) on the optimality of negotiation outcome is mediated by harmony norm when negotiating as a team but not when negotiating as solos.…”
Section: Introductionmentioning
confidence: 99%
“…For comparative purposes, it should be noted that neutral moods are slightly higher than the midpoint of the scale (e.g., 6.20) as healthy non-depressive people have a slight positive mood bias (Bless, Schwarz, Clore, Golisano, & Rabe, 1996). We have previously used these same videos and the SAM scale to successfully induce and assess negative and neutral moods (Knott & Thorley, 2014;Schnitzspahn et al, 2014).…”
Section: Stimulimentioning
confidence: 99%
“…A first study [27] observed that young, but not older adults showed impaired PM under a sad and happy mood compared to a neutral mood condition. Recently, our group conducted a study testing the effects of acute stress on PM in young and older adults.…”
Section: Major Issues For the Next Decadementioning
confidence: 99%